Estrategias para evaluar daños en eventos adversos (antrópicos y naturales) a partir de EVIN (evaluación inicial de necesidades) en la ciudad de Latacunga, provincia de Cotopaxi. - Pérez Bravo, Josselyn Anahy (2022)
This project is designed to develop a strategic guide, "EVIN", Initial Needs Assessment, which serves as a practical, fast and objective instrument to obtain real data through a format that allows recording quantitatively or qualitatively the technical survey of information on damage to people, material goods and the environment; The collection of information will be carried out through public and private entities and trained people. It is also aimed at students of the Technical University of Cotopaxi of the Environmental Engineering career, through the results obtained and analyzed, the authorities in charge of risk management will determine and address the needs of the affected or damaged areas by the possible impacts generated by adverse events, whether anthropogenic or natural; EVIN will be applied after the disaster, in the first 12 hours after the event, since in the initial hours of the event, work is done with insufficient information and in the midst of uncertainties, which is why the "EVIN" Guide has the fundamental purpose of serving as support in the strategic analysis to provide humanitarian assistance and mitigate risks in the city of Latacunga, province of Cotopaxi.